2020
DOI: 10.1186/s13561-020-00285-w
|View full text |Cite
|
Sign up to set email alerts
|

Cost of care for persons with dementia: using a discrete-time Markov chain approach with administrative and clinical data from the dementia service Centres in Austria

Abstract: Background There is growing evidence that the cost for dementia care will increase rapidly in the coming years. Therefore, the objective of this paper was to determine the economic impact of treating clients with dementia in outpatient Dementia Service Centres (DSCs) and simulate the cost progression with real clinical and cost data. Methods To estimate the cost for dementia care, real administrative and clinical data from 1341 clients of the DSCs were used to approximate the total cost of non-pharmaceutical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…This could be due to a longer follow-up time and more accurate recall in retrospective studies, increasing the likelihood of accurately capturing rare hospitalisation events. The cost for caregiver time varied substantially across methodologies; the high cost in retrospective study designs is driven by a single study reporting informal care data from an administrative database [ 33 ]. Randomised trials also reported higher costs for informal care compared with cross-sectional or prospective observational designs, potentially because of a greater use of comprehensive assessment scales for informal care.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to a longer follow-up time and more accurate recall in retrospective studies, increasing the likelihood of accurately capturing rare hospitalisation events. The cost for caregiver time varied substantially across methodologies; the high cost in retrospective study designs is driven by a single study reporting informal care data from an administrative database [ 33 ]. Randomised trials also reported higher costs for informal care compared with cross-sectional or prospective observational designs, potentially because of a greater use of comprehensive assessment scales for informal care.…”
Section: Resultsmentioning
confidence: 99%
“…We have used a model-based approach to conduct the cost-effectiveness analysis for MINT Memory Clinic care; a similar approach has also been used to evaluate the cost of illness associated with dementia,32 33 and the cost-effectiveness of health interventions for people with dementia 31. Although no other studies have compared care models similar to MINT Memory Clinic care to usual dementia care services, cost-effectiveness of other dementia care interventions has been studied with positive results 30 31 34 35.…”
Section: Discussionmentioning
confidence: 99%
“…Data sources were national studies [ 6 , 26 46 ], and therefore, they were further processed before use in the model. The first modification was to control for the different publication years.…”
Section: Methodsmentioning
confidence: 99%